Peer assessment of professional competence - Dannefer, Elaine F; Henson, Lindsey C; Bierer, S Beth; Grady-Weliky, Tana A; Meldrum, Sean; Nofziger, Anne C; Barclay, Craig; Epstein, Ronald M (Medical education, 2005)
Background  Current assessment formats for medical students reliably test core knowledge and basic skills. Methods for assessing other important domains of competence, such as interpersonal skills, humanism and teamwork skills, are less well developed. This study describes the development, implementation and results of peer assessment as a measure of professional competence of medical students to be used for formative purposes. Methods  Year 2 medical students assessed the professional competence of their peers using an online assessment instrument. Fifteen randomly selected classmates were assigned to assess each student. The responses were analysed to determine the reliability and validity of the scores and to explore relationships between peer assessments and other assessment measures. Results  Factor analyses suggest a 2‐dimensional conceptualisation of professional competence: 1 factor represents Work Habits, such as preparedness and initiative, and the other factor represents Interpersonal Habits, including respect and trustworthiness. The Work Habits factor had moderate, yet statistically significant correlations ranging from 0.21 to 0.53 with all other performance measures that were part of a comprehensive assessment of professional competence. Approximately 6 peer raters were needed to achieve a generalisability coefficient of 0.70. Conclusions  Our findings suggest that it is possible to introduce peer assessment for formative purposes in an undergraduate medical school programme that provides multiple opportunities to interact with and observe peers.